Mejoramiento e identificación de riesgos en el canal la peligrosa Marmot-Gran Chimú - Castro Linares, Carlos Cristian (2016)
This project called "IDENTIFICATION OF RISKS AND IMPROVING THE CHANNEL THE DANGEROUS MARMOT-Gran Chimu...” - IN THE DEPARTMENT OF LIBERTY determines in the first instance risk levels present along the route of the canal, identifying and weighing the dangers of a different nature to which it is exposed the canal and the town center. Make a vulnerability analysis (V) in the identified locations for evaluation and risk calculation risk (R) and the selection of appropriate prevention measures. At present in different areas of the Coast and Sierra Peruvian agricultural activity is subject to resource availability water less and less available and consequently limiting for normal development of agricultural activity, especially in times of low water supply irrigation water is of great importance in agricultural production, since this activity is the main rural areas of Peru, so it is necessary to provide a timely supply and the necessary amount of irrigation water for normal crop development . The El Nino phenomenon occurs with some recurrence, and during the years 1983, 1984, 1998, 2000 and 2001, these events are characterized by abundant rainfall both coast and mountains, as a result originate important river floods, lost crop, obstruction and destruction of irrigation canals and roads, isolation, problems in providing products and marketing, soil erosion, landslides and rockfalls. According to CENEPRED, the study "SCENARIOS RISKS BEFORE THE LIKELIHOOD OF EL NIÑO". The Marmot District and its population, according Stage Risk, in the presence of the Child would be affected. The Marmot District, in 2008 many landslides occurred as a result of incessant rains that affected public and private property. The population of Marmot District, does not have an infrastructure proper driving, water distribution is done by rustic ground channels, appreciating a great loss for leaks and poor control in water management, however irrigators do possible to perform the maintenance of its channels to effectively utilize the available water. In certain sections of the channel there is income groundwater due to a shallow water table, an interceptor drain leakage protection and control channel to prevent deterioration of the coating. The design flow is estimated 0.228 m3 / s, estimated in balance with demand maximum total supply. Starts channel starts in the Chicama River, main supply source, has a length of 12 + 481.16 ml. The channel is trapezoidal section, it arises clothe concrete fc = 175 kg / cm2, thickness 0.075 m (3 in). Along the canal it will be necessary to build various artworks, such as steep falls (No.06) and vertical (No. 15), laterals (No. 11), elevators (No. 03), a footbridge and a bridge vehicular No. (03). risk levels should be determined along the canal path DANGEROUS. Identifying and weighing the different hazards (P = E) which is exposed the town center and also performing vulnerability analysis (V) in the identified places, information necessary for evaluation and calculation of risk (R = E * V) . Risk identification (R) and their weighting expresses the probability of losses and expected damage (people, material assets, financial resources) upon the occurrence of an extreme event of natural or technological origin. Risk calculation includes an analysis and a combination of theoretical and empirical data regarding the probability of the hazard identified, ie the strength and intensity of their occurrence; as well as analysis of vulnerability or the responsiveness of the elements exposed to danger (population, housing, infrastructure, etc.), within a given geographical area. For this purpose it is necessary to build a double-entry matrix called "Matrix Risk and Vulnerability" For example: The topography of the terrain to the left side of the channel, is presented with a slightly inclined slope, which on rainy days makes the risk of possible landslides in HALF character is broken. But the biggest risk is presented by landslides and mudslides in some cases, are referred to as too high. " However various local recurrent dangers originate additional risks. The sequence in treating risks caused by widespread or local extreme events is as follows Qualitative and quantitative estimation of risk of damage in the area of intervention. The type of damage or loss generated. Loss of life, injury or ill, rehabilitation and reconstruction costs, direct impact for good or service interruption, indirect impact by interrupting the good or service. Prevention measures disaster risks (future risks), to minimize possible damage or impact of future events. Damage to family and local economy, considerable loss of infrastructure: canals, roads, electricity, water systems. Corrective measures such as running. Construction of retaining walls, complementary works slope stability, forestation and other plant species prevention. The design must also consider the maintenance and immediate and periodic (removal of solid materials) cleaning after the occurrence of landslides or mudslides, regardless of the magnitude thereof, so that the working sections keep the design area permanently. For this purpose additional budgetary resources are allocated to employees in other activities Risk control Refer to make permanent efforts to reduce and mitigate the risk, determining amounts of investment needed. Which should be implemented in a given period, according to the following scale. Moderate: When the moderate risk is associated with extremely harmful consequences, it is necessary to determine subsequent to establish more precisely the likelihood of harm, as the basis for improved control measures actions. Grave: Do not begin work until the event is completed and reduced risk. It may require considerable resources to control risk. When the risk corresponds to a job that is being done, the problem must be remedied at a lower risk of moderate weather. Very Grave: Do not start any action to prevent, or continue any work until the end of the event and until the risks have been fully reduced. If it is not possible to reduce future risk, even with considerable resources, they should be prohibited reconstruction and rehabilitation.